Magma Chamber Associated to Deep Faults in Copahue Active Volcanic Complex, South America, Suggested by Magnetotelluric Study - Borzotta, E.; Caselli, A.T.; Mamani, M.J. (Геофизический журнал, 2018)
Magnetotelluric studies were carried out in 1993 and 2008 inside the caldera of Copahue Volcanic Complex, located in South America, at the border between Chile and Argentina (37°45' S; 71°10.2' W). The main effusive centre of this complex is the Copahue Active Volcano, which constitutes an important geothermal zone. The study of the crust and the investigation of possible magma chambers were the objectives of this survey. В 1993 и 2008 гг. В кальдере вулканического комплекса Копауэ, Южная Америка, государственную границу Чили и Аргентины (S 37 ° 51'; W 71 ° 10,2') было проведено магнито-теллурическое исследование. Главный эффузивный центр этого комплекса - активный вулкан Копауэ, что является важным геотермальной зоной. Приведены результаты изучения коры и исследования возможных магматических камер. У 1993 і 2008 рр. у кальдері вулканічного комплексу Копауе, Південна Америка, державний кордон Чилі та Аргентини (S 37°51'; W 71°10,2') було проведено магніто-телуричне дослідження. Головний ефузивний центр цього комплексу — активний вулкан Копауе, що є важливою геотермальною зоною. Наведено результати вивчення кори і дослідження можливих магматичних камер.